Erratum: Severe Dysbiosis and Specific Haemophilus and Neisseria Signatures as Hallmarks of the Oropharyngeal Microbiome in Critically Ill Coronavirus Disease 2019 (COVID-19) Patients (Clin Infect Dis DOI: 10.1093/cid/ciab902) - De Castilhos, Juliana; Zamir, Eli; Hippchen, Theresa; Rohrbach, Roman; Schmidt, Sabine; Hengler, Silvana; Schumacher, Hanna; Neubauer, Melanie; Kunz, Sabrina; Mueller-Esch, Tonia; Hiergeist, Andreas; Gessner, Andre; et al. (Clinical Infectious Diseases, 2022)
Several errors appeared in supplementary data for the corrected proof publication of this article (de Castilhos J, Zamir E, Hippchen T, et al. Severe Dysbiosis and Specific Haemophilus and Neisseria Signatures as Hallmarks of the Oropharyngeal Microbiome in Critically Ill Coronavirus Disease 2019 [COVID-19] Patients. Clin Infect Dis; https://doi.org/10.1093/ cid/ciab902). • The barplots in Figure S1A were not correctly displayed due to an erroneous jitter function applied. • The functional profiling of the metagenomes was not described. The data on microbial genes and patheways were inferred from the HUMAnN3 pipeline (https://github.com/ biobakery/humann). All statistical analysis were performed by R (version 3.6.1). • The group assignments in the legends to Figures S3A and S3B contained a minor mistake. • The legends of Figures S4E and S4D were swapped. The legend of S4D should describe the SARS-CoV-2 load in pharyngeal specimens over time, while the legend of Figure S4E should specify the network visualization of target microbial species. The publisher regrets these errors.
CRIS-Team Scopus Importer:2023-03-23